Peningkatan Kompetensi Sosial Guru Melalui Workshop Guru di SDN-1 Sukajaya Tahun 2018: Improving Teacher's Social Competence Through Teacher Workshop in SDN-1 Sukajaya In 2018 - Sawadi, Sawadi (Anterior Jurnal, 2019)
The professionalism of a teacher is a must in realizing knowledge-based schools, namely an understanding of learning, curriculum, and human development including learning styles (Kariman, 2002). In general, schools that have teachers with professional competence will apply "learning by doing" to replace teaching methods where the teacher only talks and students only listen.